The Legal Aspects of the Hanging Marriage Practice: An Ethnographic Analysis - Yahanan; Afiq Budiawan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The tradition of hanging marriage in the Kampar community is part of a cultural heritage that is still preserved today. This tradition involves a series of traditional ceremonies that are full of meaning, ranging from the Khatam Al-Qur'an rituals, Barandam, night, to the marriage procession itself. Hanging marriage is not only seen as a form of prevention of pre-marital relations, but also as a symbol of spiritual and social readiness of the bride and groom before living a domestic life. In the perspective of Islamic law, this tradition does not conflict as long as it does not deviate from the Shari'a, although there are several aspects that need to be harmonized with the provisions of the National Marriage Law, especially related to the minimum age limit of marriage. This study aims to examine more in the meaning and cultural values ​​behind the tradition as well as the challenges faced in the context of children's modernization and protection